The Necessity of Continuing Professional Development for EFL Teachers - Fadl ELmula, Elgaili Mhajoub Ahmed (Gezira Journal of Educational Sciences and Humanities; مجلد 16 عدد 1 (2019), 2019)
The teaching profession involves renewed work in the ever-changing and rapidly changing world of knowledge and technology. Which requires teachers to maintain the highest standards of professional practice to perform well with this innovation and rapid change. This study aimed to investigate the process through which EFL teachers become capable of engaging in, sharing control of, influencing events and in situations that affect their work as teachers. The study also aimed at investigating EFL teachers perceptions of Continuing professional development and identifying the main characteristics of existing practices, besides offering some suggestions to improve EFL teachers Continuing professional development. The study adopted the descriptive analytical method. The data was collected with a questionnaire. The sample consist of (60) EFL teachers from EL-Hasaheisa Locality. The data were analyzed with (SPSS) programme. As the  result of the analysis it is found that: Effective Continuing professional development requires time and  space, support from the Ministry of Education. Successful Continuing professional development is often grounded in teacher collaboration . The Ministry of Education does not have a budget for EFL teacher Continuing professional development. This study recommends that: The Ministry of Education should establish Continuing teachers training centres. Opportunities should be provided to teachers to participate in more activities and Continuing training. Finally the process of Continuing professional development of EFL teachers should be monitored continually.